Microstructural changes in cement mortar due to an alkali carbonate reaction - Štukovnik, Petra (Materiali in tehnologije, 2019)
This paper investigates the process of an alkali-carbonate reaction (ACR) in cement mortar in the time frame of 1 year. The mortar bars (40 mm % 40 mm % 160 mm) were prepared using dolomite of the Triassic age from the south-eastern part of Slovenia as a source of crushed stone aggregate. As a binder, Portland cement CEM I 52.5 R was used. The hardened mortar bars were exposed to accelerated ageing conditions simulated by 1-M NaOH at 60 °C or deionized water at 60 °C, 28 d after casting. The aged mortar samples were investigated using optical microscopy, SEM and XRD. The obtained results revealed that chemical reactions characteristic for the ACR progressed in all the analysed samples. Additionally, new Mg-Al, Mg-Si and Mg-Al-Si gel-like phases were detected at the aggregate-cement paste interface. The influence of the ACR on the mechanical properties of the cement mortar was studied through the flexural and compressive strength and the elasticity modulus of mortar bars.
Keywords: alkali carbonate reaction (ACR); alkalno karbonatna reakcija (ACR); dedolomitisation; dedolomitizacija; formation of new Mg-Al, Mg-Si and Mg-Al-Si phases; oblikovanje Mg-Al, Mg-Si faz; oblikovanje Mg-Al-Si faz